Selected Lectures of the 16th International Congress on Neonatology and Pediatrics, On Demand; Cagliari (Italy); November 20th-December 31st, 2020 - - (Hygeia Press di Corridori Marinella, 2020)
Selected Lectures of the 16th International Congress on Neonatology and Pediatrics, On Demand • Cagliari (Italy) • November 20th-December 31st, 2020   LECT 1 • THE IMPACT OF ASSISTED REPRODUCTION, INTRAUTERINE GROWTH RESTRICTION AND PREMATURITY ON THE NEURODEVELOPMENT OF TWINS • D.D. Briana (Athens, Greece) LECT 2 • PFAPA (PERIODIC FEVER - APHTHOUS STOMATITIS - PHARYNGITIS - ADENOPATHY) SYNDROME: LIGHTS IN THE DARK? • S. Manti, G.F. Parisi, M. Papale, P. Barone, S. Leonardi (Catania, Italy) LECT 3 • EARLY LIFE INTERVENTIONS AND IMMUNE HEALTH RELEVANCE FOR SPECIALIZED NUTRITION • J. Garssen (Utrecht, The Netherlands) LECT 4 • COVID-19 AND KAWASAKI SYNDROME: WHAT WE KNOW • P.P. Bassareo (Dublin, Ireland) LECT 5 • HUMAN MILK AS A MAGIC FLUID • A. Dessì (Cagliari, Italy) LECT 6 • NEUROPROTECTION OF NEONATAL BRAIN TODAY • G. Buonocore (Siena, Italy) LECT 7 • PROBIOTICS: ARE ALL THE SAME? • R. Francavilla, V.N. Dargenio, F. Cristofori (Bari, Italy) LECT 8 • VITAMIN D: FROM ROOTS TO METABOLOMICS • M. Puddu (Cagliari, Italy) LECT 9 • RESPIRATORY SYNCYTIAL VIRUS: PRESENT AND FUTURE • L. Bonadies, A. Galderisi, E. Priante, V. Mardegan, E. Baraldi (Padua, Italy) LECT 10 • GROWTH: NATURE OR NURTURE? WHERE DOES INEQUALITY BEGIN? • E. Bertino, G. Maiocco, S. Sottemano (Turin, Italy) LECT 11 • OMICS IN AUTISM • M. Mussap (Cagliari, Italy) LECT 12 • PLACENTA AND NEONATAL INFECTION: INTRIGUING CONNECTIONS • G. Faa, S. Angioni, V. Vallascas, M. Moi, F. Ledda, P. Van Eyken, D. Fanni, C. Gerosa (Cagliari, Italy, and Genk, Belgium) LECT 13 • METABOLOMICS AND HUMAN MILK • V. Fanos, F. Bardanzellu, M. Puddu (Cagliari, Italy)